Social Media Marketing and Business Performance: Analyzing The TOE Framework and Relational Capability - Hafizni, Rihan; Lita, Ratni Prima; Yeni, Yulia Hendri; Syafrizal, Syafrizal (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The rapid growth of social media is presenting micro and small enterprises (MSEs) with new opportunities to expand the market reach, strengthen customer engagement, and enhance competitiveness. In Indonesia where MSEs dominate the business landscape, government initiatives strongly motivate digital adoption while the practical and strategic use of social media marketing (SMM) remains limited. Therefore, this study aimed to investigate the impact of SMM adoption on business performance by extending the Technology–Organization–Environment (TOE) framework with relational capability (RC) as a mediating construct. A quantitative design was adopted using Structural Equation Modeling (SEM) with Smart PLS 4 on survey data from 300 food-based MSEs in Central Java. The results confirmed that organizational and environmental factors significantly influenced behavioral intention and strongly predicted SMM usage. SMM was also found to have a positive impact on both RC and business performance, while RC served as a significant mediator between SMM and performance. This study contributed theoretically by integrating TOE and RC to explain digital adoption outcomes in resource-constrained contexts, and practically by outlining the need for digital upskilling and relationship-building strategies to maximize the performance benefits of SMM adoption.